Economic Origins of Cultural Norms: The Case of Animal Husbandry and Bastardy - Christoph Eder; Martin Halla (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We explore the origins of the cultural norm regarding illegitimacy and test the hypothesis that traditional agricultural production structures influenced the historical illegitimacy ratio, and have a lasting effect until today. Based on data dating back to the Austro-Hungarian Empire, we use exogenous variation in the local agricultural suitability to show that descendants from societies focusing on animal husbandry (and not crop farming) are today still more likely to have a non-marital birth.
Keywords: J13; 330